Robotic Surgery for Renal Cancer - Goonewardene, Sanchia S.; Persad, Raj.; Albala, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This latest book in the Management of Urology Series provides insight into how to appropriately manage patients undergoing pelvic robotic urological surgery for renal cancer. Extensive guidance is provided on how to perform a range of procedures including the retroperitoneal renal approach along with information on how to utilize the latest robots effectively. Cases are also presented on how to best manage complications associated with partial nephrectomy. Each chapter also contains learning objectives to assist the reader in extrapolating the key information covered. Robotic Surgery for Renal Cancer is an up-to-date overview of the latest techniques utilized in this field along with potential management strategies for these patients, making it a critical resource for urologists, oncologists, and specialist nurses.
Suturing techniques in robot-assisted partial nephrectomy (RAPN) -- Resection techniques robotic-assisted partial nephrectomy -- Clamping techniques for partial nephrectomy -- Robotic retroperitoneal partial nephrectomy -- Robotic partial nephrectomy -- Pushing the boundaries in robot-assisted partial nephrectomy for renal cancer -- Perioperative surgical complications in robotic partial nephrectomy -- Renal robotic surgery for lefties - Left-handedness in upper tract robotic surgery -- Training with new robots and how to transition from one system to the next in renal cancer surgery -- New robots and how this has changed operative technique in renal cancer surgery -- Use of indocyanine green (ICG) during robotic surgery for renal cancer -- 3D virtual models and augmented reality for robot-assisted partial nephrectomy -- Open partial nephrectomy: Current status in the minimally-invasive surgery era -- Decision-making for patients with localized renal masses -- Management of localized renal masses: The European Association of Urology (EAU), American Urological Association (AUA) and American Society of Clinical Oncology (ASCO) guidelines$1 (Bperspective -- Active surveillance and watchful waiting in renal cancer -- Ablative therapies in renal cancer -- Open radical nephrectomy -- Robotic surgery for renal cancer: Transperitoneal and retroperitoneal port placement -- Robot assisted laparoscopy for renal cancer: Transperitoneal vs retroperitoneal approach -- Robotic radical nephrectomy -- Preoperative set-up of patients undergoing robotic inferior vena cava thrombectomy -- Renal cell carcinoma with tumour thrombus: A review of relevant anatomy and surgical techniques for the general urologist -- Cytoreductive nephrectomy in metastatic renal cell carcinoma.s
Keywords: Genitourinary organs -- Surgery; Urology; Oncology; Urological Surgery; Urology; Oncology; Urologic Surgical Procedures -- methods; Robotic Surgical Procedures -- methods